Some results of analysis of hydrological monitoring observations data in the project area and in the sites of russian npps - E. G. Bugaev; A. S. Gouseltsev; A. A. Malofeev; L. F. Silaeva; L. M. Fikhieva; D. N. Gorobtsov (Известия высших учебных заведений: Геология и разведка)
The data on justification of safety of NPP’ placing in Russia in different climatic conditions is analyzed in the first time by results of hydrological monitoring observations. This analysis is based on the joint consideration of comments and recommendations of expert summaries. The necessity of improvement of hydrological monitoring observations system, more thorough use of their results in the data of justification of NPPs safety and during the design of critical values of control parameters is shown. On the basis of the latter, the prompt recommendations on realization of organizational and technical measures of safety provision under catastrophic hydrological events, including floods and freshets.